The basic conceptual of Islamic micro economy: The literature and phenomenology study - Ni’mati Rahmatika, Arivatu (Opción, 2019)
This research aims to develop the new basic concept of Islamic micro-economy based on Walisongo’s perspective via a qualitative approach by applying literature and Phenomenology research methods. The result of this research is the basic concept of Islamic micro-economy that has done by Walisongo. It is showed that trading is the rail act of economy that can develop the population’s incomes. In conclusion, there are some aspects that need to be implemented and taken into consideration in every economic activity. That is: 1)The purpose of business, 2)Rules between stakeholders and 3)The good relations between stakeholders.